PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Shofiyatul Masithoh; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
This study aims to examine the effect of the number of members of the board of commissioners, seats of independent commissioners, the frequency of board members’ meetings as an independent variable on company performance in the manufacturing sector in Indonesia. Company performance as the dependent variable is measured by and ROA (Return On Asset).The population in this study is manufacturing companies listed on the Indonesia Stock Exchange for public companies. Consisting of manufacturing companies listed on the Indonesia Stock Exchange in the period 2017. The sampling method in this study was purposive sampling with certain criteria. The number of samples used in this study were 129 samples. Data analysis in this study uses descriptive analysis, testing classic assumptions, multiple regression analysis, and testing hypotheses.The results of the analysis of this study indicate that the number of commissioners and independent commissioners has no effect on company performance. While the frequency of board members’ meetings has a positive and significant effect on company performance.